Wpływ zmian temperatury i wilgotności na cykle rozwojowe i znaczenie owadów w ekosystemach leśnych w związku z prawdopodobnymi zmianami klimatycznymi - Jaworski, Tomasz; Hilszczański, Jacek (Leśne Prace Badawcze, 2013)
Ongoing climate change is mainly evident as increased in average temperature. It is expected to have a significant impact on world’s biomes, with forest ecosystems especially vulnerable to these changes. The effect of climate change on forests is both indirect, through its impact on various tree species of different ecological requirements, and direct, through its impact on all living components of the forest ecosystem. Among the latter, insects are the group of the greatest importance, including species detrimental to forest health. The impact of climate change on forest insects may be reflected in their distribution, phenology, activity, number of generations and, indirectly, through impact on their natural enemies. Predicting the future direction and pace of the climate change, as well as direct and indirect consequences of its effect on forest insects is difficult and often subject to considerable inaccuracy. The paper presents a review of data from the published literature in this area of study. The influence of the basic climate parameters, temperature and humidity, on forest herbivore insects is discussed, particularly in the context of the most probable scenarios of climate change, i.e. the gradual increase in the average temperature. Observed and projected impacts of climate change in relation to the influence of herbivorous insects on forest ecosystems are characterized. We present some of the possible adaptation strategies of forest management to the expected climate changes.